UTILIZATION OF CORN (Zea mays) AS A COMBINATION INGREDIENT IN TOFU PRODUCTION WITH THE ADDITION OF IE ASAM SUNTI EXTRACT AND IE KULOH SIRA EXTRACT AS NATURAL COAGULANTS - Radhia Ulfa Rahmi; S Salmyah; Ratna Sari (Politeknik Negeri Lhokseumawe, 2026)
This study aims to examine the effect of coagulant volume and the addition of corn on the characteristics of tofu. The method used is Central Composite Design (CCD), which is part of the Response Surface Methodology (RSM), along with organoleptic testing to assess consumer acceptance. The raw material variations consist of combinations of soybean and corn in the ratios of 900 g:100 g, 800 g:200 g, 700 g:300 g, 600 g:400 g, and 500 g:500 g, as well as coagulant volumes of ie asam sunti and ie kuloh sira ranging from 100 to 300 ml. The results showed that the best combination was 700 grams of soybean and 300 grams of corn with 250 ml of ie asam sunti, producing a texture of 200 mm/second, pH 5.6, protein content of 5.6%, and a yield of 75%. Meanwhile, 250 ml of ie kuloh sira produced a texture of 240 mm/second, pH 5.8, protein content of 5.8%, and a yield of 75%. Organoleptic testing was conducted using a hedonic scale to determine consumer preference for the resulting tofu. The evaluation covered aroma, taste, and color, which are important indicators of the acceptability of corn tofu products..Keywords: ie asam sunti, ie kuloh sira, soybean, corn tofu